MODULUS OF ELASCITY OF UNFIRED RAMMED EARTH - Barbora Mužíková; Tereza Plaček Otcovská; Pavel Padevět (Acta Polytechnica CTU Proceedings)
The article is focused on measurement and evaluation of elastic modulus of unfired rammed earth and determination of stress-strain curve in compressive test. Sets of different containt of clay, sand and water were made and their properties were evalueted and compared. It was found out that for the hightest elascity modulus is ideal the ratio of sand and clay around 75/25 up to 80/20, the sets with montmorillonite clay had substantialy smaller value of elascity modulusthan the sets with illite-kaolinite clay and the ideal content of water for sand/clay ratio 75/25 is around 0.295.